A non-baseline algorithm for damage locating in flexural structures using dynamic distributed macro-strain responses. - Li, S. Z.
The concept of distributed strain-sensing techniques has been proposed in our recent research, which was dedicated to utilizing the strain distributions throughout the full or partial areas of structures to detect arbitrary and unforeseen damage. An algorithm not requiring a detailed analytical model is presented for damage locating in flexural structures through the direct use of dynamic responses recorded by distributed long-gauge strain sensors. The modal macro-strain vector (MMSV), which has been proven to have a mapping relation with displacement mode shape, can be extracted directly from macro-strain time-series data, from which a damage evaluating index can be derived and used as an indicator for locating damage. Numerical examples are simulated to verify the sensitivity and effectiveness of the index in different cases. Furthermore, experimental investigations on a cantilevered beam with various long-gauge fibre optic sensors placements are carried out to examine the feasibility and applicability of the proposed method.
Keywords: Damage locating; Non-baseline.; Dynamic; Distributed macro-strain response; Long-gauge fibre optic sensor; Flexural structure